Pengaruh Fan Loyalty, Pre-Order Benefit, Dan Perceived Value Terhadap Keputusan Pembelian Album ‘Pleasure’ Pada Komunitas Treasure Maker Di Aplikasi X (Twitter) - Zalika Umairah; Indawati Lestari (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
The rapid growth of the K-pop industry has led to high levels of fan engagement in supporting their idols, not only through digital music consumption but also through the purchase of physical albums that offer various added values. This study aims to examine the effects of fan loyalty, pre-order benefits, and perceived value on purchase decisions of the Pleasure album among the Treasure Maker community on the X (Twitter) platform. This research employs a quantitative approach. Data were collected through the distribution of questionnaires to members of the Treasure Maker community who are active on X and were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The research sample consisted of 100 respondents who are Treasure Makers, selected using purposive sampling. The results indicate that fan loyalty, pre-order benefits, and perceived value have a positive and significant effect on purchase decisions of the Pleasure album. This study is expected to contribute to entertainment companies in designing effective marketing strategies by considering the characteristics and behavior of K-pop fans in a sustainable manner within the entertainment industry.